EKSTRAKURIKULER DASAR PEMROGRAMAN UNTUK SMA CANDRA NAYA JAKARTA - Haris, Darius Andana; Sylvanus, Jericho; Xaverius, Vincentius; Puendra, Valentino (Jurnal Serina Abdimas, 2024)
Advances in information and communication technology are also important factors that help in many ways. Everything that happens online is increasingly pushing forward the progress of information and communication technology. Game development using Unity is a form of information and communication technology product. Due to the rapid growth and popularity of game development, we support courses for a large number of multimedia majors. At school level, especially at senior secondary level, game development can be studied through workshop activities. Workshop activities enable high school students to more quickly develop their potential and utilize the knowledge gained as preparation for facing the world of higher education. This workshop activity also functions as a forum to help students improve their non-academic results. Similar PKM has been implemented in extracurricular classes and received a positive response. Sinar Dalma High School, which previously won competitions held through PKM, has now started the Unity Basic extracurricular. PKM implementation is divided into several stages: needs assessment, material development, and workshop implementation. ABSTRAK Kemajuan teknologi informasi dan komunikasi juga menjadi fakto penting yang membantu dalam banyak hal. Segala sesuatu yang terjadi secara online semakin mendorong kemajuan teknologi informasi dan komunikasi. Pengembangan game menggunakan Unity merupakan salah satu bentuk produk teknologi informasi dan komunikasi. Karena pesatnya perkembangan dan popularitas pengembangan game, kami mendukung perkuliahan untuk sejumlah besar jurusan multimedia. Di tingkat sekolah, khususnya di tingkat menengah atas, pengembangan permainan dapat dipelajari melalui kegiatan workshop. Kegiatan workshop memungkinkan siswa SMA untuk lebih cepat mengembangkan potensinya dan memanfaatkan ilmu yang didapat sebagai persiapan menghadapi dunia pendidikan tinggi selanjutnya. Kegiatan workshop ini juga berfungsi sebagai wadah untuk membantu mahasiswa meningkatkan hasil non-akademiknya. PKM serupa sudah pernah dilaksanakan di kelas ekstrakurikuler dan mendapat respon positif. SMA Sinar Dalma yang sebelumnya pernah menjuarai lomba-lomba yang dilakukan melalui PKM, kini telah memulai ekstrakurikuler Unity Basic. Pelaksana PKM dibagi dalam beberapa tahap: pengkajian kebutuhan, pengembangan materi, dan pelaksanaan lokakarya.